Money for Ireland : finance, diplomacy, politics, and the first Dáil Éireann loans, 1919-1936 - Carroll, Francis M. (Praeger studies in diplomacy and strategic thought., 2002)
Raising money was one of the great successes of the Irish government, as the funds provided the "sinews of war" with which to fight Britain. This book details the history of the financing of the Irish revolution from both domestic and international loans. Divisions in Irish society over the Anglo-Irish Treaty and the creation of the Irish Free State led to the outbreak of Civil War. The Free State's ability to deny the anti-Treaty forces access to the loan funds through a ten-year court battle would prove a powerful weapon in defeating the Republicans